Impact of body characteristics on ultrasound-measured inferior vena cava parameters in Chinese children - Jianjun Gui; Boyang Zhou; Juanhua Liu; Bing Ou; Yue Wang; Longyuan Jiang; Wanchun Tang; Baoming Luo; Zhengfei Yang (Brazilian Journal of Medical and Biological Research)
Ultrasound-measured inferior vena cava (IVC) and abdominal aorta (Ao)-associated parameters have been used to predict volume status for decades, yet research focusing on the impact of individual physical characteristics, including gender, height/weight, body surface area (BSA), and age, assessed simultaneously on those parameters in Chinese children is lacking. The aim of the present study was to explore the impact of individual characteristics on maximum IVC diameter (IVCmax), Ao, and IVCmax/Ao in healthy Chinese children. From September to December 2015, 200 healthy children from 1 to 13 years of age were enrolled. IVCmax and Ao diameters were measured by 2D ultrasound. We found that age (years), height (cm), weight (kg), waist circumference (cm), and BSA (m2) were positively correlated with IVCmax and Ao. Multivariate linear regression showed that age was the only independent variable for IVCmax (mm) in female children, height was the only independent variable for IVCmax in male children, and age was the only independent variable for Ao in both females and males. IVCmax/Ao was not significantly influenced by the subjects’ characteristics. In conclusion, IVCmax and Ao were more susceptible to subjects’ characteristics than IVCmax/Ao. IVCmax/Ao could be a reliable and practical parameter in Chinese children as it was independent of age, height, and weight.